2021
DOI: 10.1126/sciadv.abf6744
|View full text |Cite
|
Sign up to set email alerts
|

Multiple substrate recognition by yeast diadenosine and diphosphoinositol polyphosphate phosphohydrolase through phosphate clamping

Abstract: The yeast diadenosine and diphosphoinositol polyphosphate phosphohydrolase DDP1 is a Nudix enzyme with pyrophosphatase activity on diphosphoinositides, dinucleotides, and polyphosphates. These substrates bind to diverse protein targets and participate in signaling and metabolism, being essential for energy and phosphate homeostasis, ATPase pump regulation, or protein phosphorylation. An exhaustive structural study of DDP1 in complex with multiple ligands related to its three diverse substrate classes is report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
(93 reference statements)
0
17
0
Order By: Relevance
“…13A ). Note that Aps1-type IPP pyrophosphatase enzymes are also active as endopolyphosphatases ( 38 , 39 ), raising the possibility that the increase in polyphosphate in aps1 Δ cells reflects a contribution of Aps1 to polyphosphate turnover. The salient finding here is that the increase in polyphosphate content in the spx1 Δ strain is eliminated in asp1 Δ spx1 Δ and asp1-D333A spx1 Δ double mutants, where the polyphosphate levels mirror those of the asp1 Δ and asp1-D333A single mutants ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…13A ). Note that Aps1-type IPP pyrophosphatase enzymes are also active as endopolyphosphatases ( 38 , 39 ), raising the possibility that the increase in polyphosphate in aps1 Δ cells reflects a contribution of Aps1 to polyphosphate turnover. The salient finding here is that the increase in polyphosphate content in the spx1 Δ strain is eliminated in asp1 Δ spx1 Δ and asp1-D333A spx1 Δ double mutants, where the polyphosphate levels mirror those of the asp1 Δ and asp1-D333A single mutants ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While data from earlier literature suggested that 1-InsP 7 rather than 5-InsP 7 is the ideal substrate for DDP1 (Lonetti et al ., 2011), a more recent study shows that DDP1 can also hydrolyze 5-InsP 7 , and preferentially hydrolyzes the 5-position PP bond from 1,5-InsP 8 rather than from the 1-position in vitro (Kilari et al ., 2013). A very recent and extensive crystallography study provides a molecular explanation for this in that PP-InsPs have several binding modes in the DDP1 catalytic pocket, with some being more productive for hydrolysis than others (Márquez-Moñino et al ., 2021). This work established that 1-InsP 7 binds in a more productive mode, whereas 5-InsP 7 molecules bind less productively within DDP1.…”
Section: Discussionmentioning
confidence: 99%
“…Although DDP1 can also act on other substrate signaling molecules in yeast and animals, there is currently no evidence to suggest that these other potential substrates are present in plants. These alternative substrates include two distinct types of molecules: polyphosphates (polyP; polyP n ) and diadenosine polyphosphates (Ap n As; specifically, Ap 5 A and Ap 6 A), which are known substrates for DDP1 in S. cerevisiae (Safrany et al ., 1999; Lonetti et al ., 2011; Andreeva et al ., 2019; Márquez-Moñino et al ., 2021). Both molecular classes have also been linked to maintaining P i metabolism and cellular homeostasis in a variety of prokaryotic and eukaryotic organisms (Lorenzo-Orts et al ., 2020; Pietrowska-Borek et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig.12Role of H bonding to coordinated water molecules in Mg(II) complexes. Top: 6WOD (disordered 6WOE is analogous, both structures contain the same Homo sapiens hydrolase); 56 bottom: 7AUU 57. Octahedral coordination mode is almost unchanged from structure to structure (yeast hydrolase).…”
mentioning
confidence: 99%